Determination of acetylcholinesterase and α-glucosidase inhibition by electrophoretically-mediated microanalysis and phenolic profile by HPLC-ESI-MS/MS of fruit juices from Brazilian Myrtaceae Plinia cauliflora (Mart.) Kausel and Eugenia uniflora L. Issue 18 (16th September 2020) - Siebert, Diogo Alexandre; de Mello, Flávia; Alberton, Michele Debiasi; Vitali, Luciano; Micke, Gustavo Amadeu
Abstract: Alzheimer's disease and diabetes mellitus are contemporary diseases of great concern. Phenolic compounds are linked to several health benefits and could lead to novel strategies to combat these ailments. The objective of this study was to evaluate by electrophoretically-mediated microanalysis the potential inhibitory activity of the fruit juices from Plinia cauliflora ("jaboticaba") and Eugenia uniflora ("pitanga") toward acetylcholinesterase (AChE) and α-glucosidase, target enzymes in strategies for the treatment of these diseases. The phenolic profiles of the samples were also investigated. Jaboticaba and pitanga juices inhibited 85.90 ± 1.73 and 52.67 ± 1.24% of AChE activity at 5 mg mL −1, and 57.91 ± 2.60 and 69.47 ± 2.89% of α-glucosidase activity at 1 mg mL −1, respectively. Total phenolic content of the juices were 303.54 ± 28.28 and 367.00 ± 11.42 mgGA L −1, respectively. The observed inhibitory activity can be explained, at least in part, by the presence of the phenolic compounds. Graphical Abstract: